УкраїніHistory of the development of customs systems and policies in the Netherlands and Ukraine - Moroz, Sofiia Volodymyrivna; Slastonenko, Oksana Oleksandrivna; Сластьоненко, Оксана Олександрівна; Мороз, Софія Володимирівна (Київ, 2024)
The thesis examines the historical development of the Ukrainian and Dutch customs systems.

Розглядається історичний шлях утворення української та нідерландської митних систем.
Історія розвитку митних систем та митної політики в Нідерландах та
Keywords: the history of Dutch customs; The Customs Code of Ukraine; history of customs; creating and developing their customs systems; історія Голландської митниці; Митний кодекс України; історія митної справи; створення та розвиток митних систем